Comparison of 111In-DOTA-NOC and 111I-DOTA-TATE distribution in the target and dose-limiting tissues: conflicting results in vitro and in vivo - Cihlo, Jan; Melicharová, Ludmila; Petrik, Milos; Laznickova, Alice; Laznicek, Milan (Anticancer research, 2008)
BACKGROUND: In this study, some important biological characteristics of two radiolabelled somatostatin analogues 111In-DOTA-1-Nal3-octreotide (DOTA-NOC) and 111In-DOTA-Tyr3-octreotate (DOTA-TATE) were compared. MATERIALS AND METHODS: Rats were used for in vivo biodistribution experiments and in vitro cell models (OK and AR42J cell lines) were used for simulating the internalization in the kidney and in subtype 2 somatostatin receptor (SSTR2)-positive tissues, respectively. RESULTS: Significantly higher radioactivity concentrations in rat organs with high density of somatostatin receptors after 111In-DOTA-NOC administration in comparison with 111In-DOTA-TATE were observed. The predominant urine excretion was associated with accumulation of the radioactivity in the kidney, where higher retention of 111In-DOTA-TATE compared to 111In-DOTA-NOC was detected. In the OK cell line the opposite results were found. No significant differences in the in vitro internalization and externalization of radioactivity to AR42J cell line were found for either peptide suggesting their same affinity for SSTR2. CONCLUSION: Preclinical experiments indicated that 111In-DOTA-NOC is a very promising peptide for somatostatin receptor-positive tumour visualization. The conflict between the in vitro and in vivo kidney handling showed that the transfer of results from in vitro to in vivo conditions and their interpretation should be performed very carefully because both types of experiments can be affected by different factors, making their simple comparison difficult.
Keywords: Chromatography, High Pressure Liquid; Kidney Tubules; nádory slinivky břišní; ledvinové kanálky; vačicovití; tkáňová distribuce; receptory somatostatinu; krysa rodu Rattus; Indium Radioisotopes; oktreotid; Organometallic Compounds; zvířata; potkani Wistar; Octreotide; organokovové sloučeniny; buněčné linie; Cell Line; Rats, Wistar; Male; Pancreatic Neoplasms; radioizotopy india; Opossums; Receptors, Somatostatin; nádorové buněčné linie; Rats; Animals; Cell Line, Tumor; mužské pohlaví; radiofarmaka; vysokoúčinná kapalinová chromatografie; Tissue Distribution; Radiopharmaceuticals